Multiple mini interview (MMI) - student selection 2025/2026 - Mohd Tambeh, Siti Norashikin (Faculty of Medicine, 2025)
The Multiple Mini Interview (MMI) is a crucial component of the MBBS admission process at the Faculty of Medicine, Universiti Teknologi MARA (UiTM). Designed to evaluate non-cognitive attributes essential for the medical profession, the MMI offers a fair, structured, and comprehensive assessment of each